SENSE OF PLACE WITHIN THE ENVIRONMENTAL ELEMENT IN CULTURAL FRAME: A REVIEW - Che Kasim, Asmma'; Azizan, Muhammad Uzair; Hussin, Khadijah (Journal of Technology Management and Business, 2016)
The numerous aspects of physical as well as the subjective features of environmental elements can affect social behavior and social interactions. The designated environmental element such as green open space, landscapes, water body as well as other environmental amenities that are bestowed by the nature such as natural weather, natural weather routes, natural topography and natural can provide amenities and benefits that contribute to the quality of life. The study is attempted to discover individual’s perception, experience and responses towards their surroundings based on elements that relate to their culture. Despite of land scarcity, new developments do not seem to recognize and respect the importance of cultural aspect resulting in the disorientation of residential property development area. Furthermore, the land use pressures are interrelated internally for fiscal benefits and externally for creating the preserve land for habitat. The literature reviewed in terms of sense of place was conducted to rediscover the fundamental conception of place, perception and experience. This paper was born from the attempt to understand why people fall in love with places and extends an ongoing progress of a study about the environmental elements in the context of culture. The concept of sense of place appeared to explain much of the ways in which people relate to place, and for this reason, many of the works reviewed for this study were written by scholars who have analyzed this concept. Hence, the background of reviewed study was to structure the work and concludes that places will add the value to establish the urban setting and place in economics context.